Pengaruh Csr Terhadap Trust, Satisfaction Dan Loyalty - Albertus Maria Setyastanto; Dwi Ferdiyatmoko Cahya Kumoro; Marhaendro Purno (Journal Of Communication Education, 2018)
ABSTRACT- This research aims to analyzethe influence of Corporate socialresponsibility to Trust, Satisfaction andloyalty is very important for marketingmanager decision making. The study wasconducted on consumers who had purchasedat least 4 times for the last 2 years, did acomplaint, and opened website of GarudaIndonesia. took 200 samples. The methodused is non-probability sampling method withpurposive sampling technique and usingStructural Equation Model (SEM) analysistool.The results of this study are (1) Corporatesocial responsibility has a positive effect onTrust. (2) Corporate social responsibility has apositive effect on Satisfaction. (3) Corporatesocial responsibility has a positive effect onLoyalty. (4) Trust has a positive effect onSatisfaction. (5) Satisfaction positively affectsLoyalty.Keywords: Corporate social responsibility,Trust, Satisfaction, Loyalty.